Boosting starch productivity of mixotrophic duckweed via light and organic carbon treatment. (June 2023) - Sun, Zuoliang; Zhao, Zekang; Zhou, Zhentao; Yang, Jingjing; Xia, Manli; Chen, Yan; Li, Xiaozhe; Ba, Sang; Lim, Boon Leong; Zhao, Xuyao; Hou, Hongwei
Abstract: Duckweeds is the most promising nonfood feedstock for sustainable bioenergy production. Mixotrophy is the best growth mode compared to photoautotrophy and heterotrophy for biomass and starch accumulation in duckweed. This work investigated the impacts of light intensities (3, 000, 6, 000, 9, 000, 12, 000, 15, 000, and 20, 000 lux) and exogenous glucose concentrations (5, 10, 15, 20, 30, and 40 g L −1 ) on the biomass and starch accumulation of mixotrophic duckweed. The results showed that increasing light intensity and the initially applied concentration of glucose enhanced both growth and starch content. However, high concentrations of glucose (15–40 g L −1 ) resulted in a higher biomass yield but concurrently greatly inhibited photosynthesis. Moreover, excess carbon was redirected into starch biosynthesis under high glucose. The maximum starch yield of 655.4 g m −2 was obtained at 40 g L −1 glucose, with a maximum starch content of 72.7% of dry biomass and a biomass yield of 1024.6 g m −2 . The optimum light intensity for starch accumulation was 20, 000 lux, with a maximum starch yield of 236.2 g m −2 . These results indicated that high organic carbon levels are a robust way to promote starch production in mixotrophic duckweed. Highlights: High glucose levels and light intensities boosted biomass and starch production. Higher glucose levels provided a higher biomass while inhibiting photosynthesis. More carbon was allocated to starch biosynthesis with higher glucose levels. 20, 000 lux was the optimum light condition for duckweed starch accumulation. The maximum starch yield of 95.7 t/ha/year was generated at 40 g/L of glucose.